Türkiye’de atkılı örme makinelerin gelişimi ve örme modasına etkisi - Taheri, Gholamreza (My University, 2019)
Bu tezin amacı Türkiye’de sanayileşmeden sonara örme sektöründe makinelerinteknik açısından gelişimi ve bu gelişimlerin örme sektöründe tasarım ve statik yönünüaraştırmaktır. Bu nedenle başta örme tarihini araştırıp ve bu gelişmelerin başlangıçnoktasından sanayi devrime kadar örme makinelerin gelişimini takıp edip ve bugelişmelerin nasıl adım adım sektörün şu anki duruma geldiğini göstereceğiz.Bu araştırma sürecinde Türkiye’de ilk örme sanayisinde temeli atan ve öncü olanfirmaların arşivini ve tarihçesini inceleyip ve sektörün etkisini göstermeye çalışacağız.

The objective of this thesis after the development of industrialization in Turkeyin terms of technology and design in the knitting machine knitting industry sector is toinvestigate whether these development and activate the static direction. There for, we willfirst investigate the history of knitting and follow the development of knitting machinesfrom the starting point of these development to the industrial revelation, and show howthese development step by step become the sector.Laid the foundation of the first knitting industry in turkey in this research processand analyse the archive and the history of the company and pioneer going to show theimpact of the sector.
Keywords: Fine arts education; Güzel sanatlar eğitimi; Örme- Örme tarihi-Örme Makinesi-Moda-Moda Tarihi--Teknik tekstil- Ev Tekstil Knitting-Knitting History-Knitting Machine- Fashion-Fashion History--Technical Textile- Home Textile; Tekstil; Textile